2022
DOI: 10.1371/journal.pntd.0010636
|View full text |Cite
|
Sign up to set email alerts
|

Randomized single oral dose phase 1 study of safety, tolerability, and pharmacokinetics of Iminosugar UV-4 Hydrochloride (UV-4B) in healthy subjects

Abstract: Background UV-4 (N-(9’-methoxynonyl)-1-deoxynojirimycin, also called MON-DNJ) is an iminosugar small-molecule oral drug candidate with in vitro antiviral activity against diverse viruses including dengue, influenza, and filoviruses and demonstrated in vivo efficacy against both dengue and influenza viruses. The antiviral mechanism of action of UV-4 is through inhibition of the host endoplasmic reticulum-resident α-glucosidase 1 and α-glucosidase 2 enzymes. This inhibition prevents proper glycan processing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Decrease in viremia, viral burden, and inflammatory cytokines, and improved survival in immunocompromised mouse model of DENV infection [ 53 •] Clinical trials for dengue prophylaxis in healthy individuals (NCT05201794) as well as for dengue therapy in patients with confirmed dengue fever (NCT04906980) are in progress Ivermectin Antiviral agent that inhibits host nuclear import receptors Reduced viral replication in vitro [ 56 , 57 ] Randomized double-blind placebo-controlled trial ( n = 203) showed faster NS1 antigenemia clearance but no improvement in virological or clinical efficacy (NCT02045069) [ 58 •] AT-752 Guanosine nucleotide analog inhibiting NS5 RdRp function, inhibits viral replication Reduced viremia on certain days and improved survival in immunocompromised mice models infected with DENV [ 63 ] Phase 1 (NCT05366439) and phase 2 (NCT05466240) clinical trials are in progress Doxycycline Tetracycline class antibiotic, inhibits viral entry and replication by inhibiting NS2B-NS3 Antiviral activity against all four DENV serotypes in vitro [ 64 ] One randomized clinical trial ( n = 231) showed reduction in inflammatory cytokines and another case control study ( n = 120) showed faster platelet recovery, leukocyte count, and reduced length of hospitalization. Clinical trials to test efficacy of doxycycline as a dengue therapeutic in pediatric (CTRI/2018/01/011548) and adult (CTRI/2021/09/036661) populations are on-going Eltrombopag Thrombopoietin receptor agonist Nil Randomized open-label placebo-controlled trial ( n = 101) showed improved platelet recovery, increased platelet count, and reduced bleeding manifestations in grade II DHF patients (SLCTR/2019/037) [ 39 •] UV-4B Endogenous alpha glucosidase inhibitor Antiviral activity in vitro [ 70 ] and in vivo [ 71 ] Phase 1a clinical trial (NCT02061358) with healthy subjects indicated that a single dose up to 1000 mg of UV-4B was safe and well tolerated [ 72 ] Zanamivir Neuraminidase inhibitor to block desialylation on platelet membrane Reduction in DENV2 NS1-induc...…”
Section: Development Of Therapeutics Targeting Dengue Virusmentioning
confidence: 99%
See 2 more Smart Citations
“…Decrease in viremia, viral burden, and inflammatory cytokines, and improved survival in immunocompromised mouse model of DENV infection [ 53 •] Clinical trials for dengue prophylaxis in healthy individuals (NCT05201794) as well as for dengue therapy in patients with confirmed dengue fever (NCT04906980) are in progress Ivermectin Antiviral agent that inhibits host nuclear import receptors Reduced viral replication in vitro [ 56 , 57 ] Randomized double-blind placebo-controlled trial ( n = 203) showed faster NS1 antigenemia clearance but no improvement in virological or clinical efficacy (NCT02045069) [ 58 •] AT-752 Guanosine nucleotide analog inhibiting NS5 RdRp function, inhibits viral replication Reduced viremia on certain days and improved survival in immunocompromised mice models infected with DENV [ 63 ] Phase 1 (NCT05366439) and phase 2 (NCT05466240) clinical trials are in progress Doxycycline Tetracycline class antibiotic, inhibits viral entry and replication by inhibiting NS2B-NS3 Antiviral activity against all four DENV serotypes in vitro [ 64 ] One randomized clinical trial ( n = 231) showed reduction in inflammatory cytokines and another case control study ( n = 120) showed faster platelet recovery, leukocyte count, and reduced length of hospitalization. Clinical trials to test efficacy of doxycycline as a dengue therapeutic in pediatric (CTRI/2018/01/011548) and adult (CTRI/2021/09/036661) populations are on-going Eltrombopag Thrombopoietin receptor agonist Nil Randomized open-label placebo-controlled trial ( n = 101) showed improved platelet recovery, increased platelet count, and reduced bleeding manifestations in grade II DHF patients (SLCTR/2019/037) [ 39 •] UV-4B Endogenous alpha glucosidase inhibitor Antiviral activity in vitro [ 70 ] and in vivo [ 71 ] Phase 1a clinical trial (NCT02061358) with healthy subjects indicated that a single dose up to 1000 mg of UV-4B was safe and well tolerated [ 72 ] Zanamivir Neuraminidase inhibitor to block desialylation on platelet membrane Reduction in DENV2 NS1-induc...…”
Section: Development Of Therapeutics Targeting Dengue Virusmentioning
confidence: 99%
“…In vivo studies using immunosuppressed mice showed decreased viremia and viral burden and improved survival in a lethal ADE model of dengue disease [ 71 ] . A Phase 1a clinical trial (NCT02061358) with healthy subjects, evaluating the safety, tolerability, and pharmacokinetics of the drug, indicated that a single dose of up to 1000 mg UV-4B was safe and well tolerated [ 72 ]. The efficacy of this drug in dengue patients has yet to be determined.…”
Section: Development Of Therapeutics Targeting Dengue Virusmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibiting the activity of the α-glucosidase is 1 strategy that can be employed in the treatment of diabetes [24,25]. Miglitol consumption is currently the most popular treatment for diabetes mellitus and is considered to be one of the standard therapies for the disease [26]. In this study, computational predictions showed that 2 Averrhoa bilimbi flower compounds which have the highest RT value, specifically tautomycetin (−6.2 kcal/mol) and lithocholic acid (−10.0 kcal/mol), showed better binding affinity values than miglitol (−5.4 kcal /mol).…”
Section: Identification Of Compounds In the Most Active Fractions Wit...mentioning
confidence: 99%
“…Iminosugars are a diverse class of hydroxylated carbohydrate mimics, some of which competitively inhibit ER α-glucosidases [ 5 ]. These molecules can interfere with host N-linked glycosylation, conferring broad-spectrum antiviral activity in vitro and in vivo [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In order to consider the potential applicability of iminosugar treatment for CCHF patients, at least two mechanistic angles should be considered.…”
Section: Introductionmentioning
confidence: 99%